Kidney function changes and their relation with the progression of cerebral small vessel disease and cognitive decline - Jiménez-Balado, Joan; Riba-Llena, Iolanda; Pizarro, Jesús; Palasí, Antoni; Penalba, Anna; Ramírez, Clara; Maisterra, Olga; Espinel, Eugenia; Ramos, Natalia; Pujadas, Francesc; Serón, Daniel; Delgado, Pilar (Journal of the neurological sciences, 2020)
We aimed to study whether worsening in markers of kidney function parallels the progression in cerebral small vessel disease (cSVD) and cognitive decline. Data from the ISSYS (Investigating Silent Strokes in Hypertensives Study), a longitudinal population-based study in hypertensives aged 50–70 and dementia and stroke-free at baseline. At both visits, patients underwent a brain MRI, a cognitive diagnosis (normal aging or mild cognitive impairment, [MCI]) and urine and blood sampling collection. We assessed the incidence of infarcts and cerebral microbleeds, and the progression of white matter hyperintensities at periventricular (PVH) and deep areas. We determined changes in albumin-creatinine ratio and estimated glomerular filtration rate (eGFR). These changes were dichotomized into microalbuminuria at follow-up —either in subjects with or without baseline microalbuminuria— and significant decline in eGFR —lowest quintile of eGFR change (−10.57 mL/min/1.73m2)—. 360 patients were followed-up for 4 years. 80 (23%) patients presented microalbuminuria at follow-up and 68 (20.1%) experienced a significant eGFR decline. Considering cSVD change, we found a relationship between microalbuminuria at follow-up and progression in PVH (β = 0.31, P-value = .01). Regarding cognitive decline, presence of microalbuminuria at follow-up related to a steeper decrease in memory function (β = −0.36, P-value<.01). Moreover, patients with significant decline in eGFR were at higher risk of incident MCI (OR = 3.54, P-value = .02). These associations were independent of progression of cSVD. The worsening in markers of kidney function paralleled the decrease in cognition and the progression of cSVD, and this may be explained by common shared underlying risk factors. •We studied the changes in markers of kidney function, cognition and vascular lesions.•Microalbuminuria was associated with progression of periventricular hyperintensities.•We found a correlation between the increase in albuminuria and memory decline.•Decline in kidney function predicted the incidence of mild cognitive impairment.•The relationship between brain and kidney may be explained by shared etiologies.